It's all good : delicious, easy recipes that will make you look good and feel great - Paltrow, Gwyneth, 1972- (Grand Central Life & Style, 2013)
Together with Julia Turshen, Paltrow compiled a collection of 185 delicious, easy recipes--free of gluten and sugar, and low in fat--that will help you stay healthy, feel more energetic and look great. Recipes include: huevos rancheros, Korean chicken tacos, salmon burgers with pickled ginger, even power brownies, banana "ice cream", and more!--